Long illness : a practical guide to surviving, healing, and thriving - Jobson, Meghan; Morgan, Juliet (Psychiatrist) (Hachette Go, 2023)
"In 2020, a surge of long-haul COVID-19 patients came to Drs. Jobson and Morgan's clinics and one thing was clear to them: We have seen this before. The pattern was strikingly similar to other long conditions: fibromyalgia, chronic fatigue syndrome, chronic pain, post-infectious syndromes, and autoimmune diseases. And that is because long illnesses manifest in similar ways. They follow patterns in the body as the result of inflammation, trauma, and toxic stress. Whether it's chronic pain, long COVID-19, or any of the myriad conditions that require long-term maintenance, people with long illnesses have been invalidated by a lack of assistance and care. The public health crisis of long COVID-19 highlighted these inequities. Drs. Jobson and Morgan are on the front lines of research and treatment; while at UCSF, they have developed an integrative program that goes beyond conventional medicine (which struggles to understand long illness). Their approach uses evidence-based integrative medicine that addresses the whole person: body, mind, and spirit. Not only do they legitimize long illness, but they also offer an unparalleled, holistic approach to healing. Drs. Jobson and Morgan empower readers by giving them expansive, accessible recovery tools: from cognitive behavioral therapy (CBT), traditional Eastern medicine, and mindfulness practices, to emerging therapies, self-healing techniques, and cutting-edge research. They also offer support and validation, with survivor stories and journaling prompts woven throughout for an interactive healing exercise. By the end of this book, readers will be equipped with the tools to accelerate their healing."--